1884 N.Y. Laws 47 - (:unkn) unknown (My University, 1884)
Ch. 46, § 8: Prohibited using, intent to use, or carrying concealed any slung-shot, billy, sand-club, metal knuckles, dagger, dirk, dangerous knife. Violators guilty of a felony
Keywords: POSSESSION - NON-GUN ARMS